ijsr 2020
DOI: 10.36106/ijsr/3733490
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 3% Hypertonic Saline and Mannitol for Brain Relaxation During Elective Supratentorial Brain Tumour Surgery

Abstract: Brain tumours may cause disturbances of cerebral auto-regulation & the blood brain barrier (BBB). These effects could possibly have an unfavourable influence on brain condition. To compare the effects of the application of a bolus hypertonic saline with those of mannitol on intraoperative brain relaxation. Ninety patients of ASA grade II and III in the age group >18 years with supratentorial brain tumours posted for elective brain tumour surgery were studied in the current study. They were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The mean intraoperative fluid input in Group H was 1312 ± 158 ml and 1340 ± 140 ml in Group M. We observed no significant difference between the groups (P > 0.05). Our findings are similar to earlier studies 14,15 .…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The mean intraoperative fluid input in Group H was 1312 ± 158 ml and 1340 ± 140 ml in Group M. We observed no significant difference between the groups (P > 0.05). Our findings are similar to earlier studies 14,15 .…”
Section: Resultssupporting
confidence: 94%
“…Being an osmotic diuretic, infusion of mannitol leads to significant diuresis. Earlier studies also found similar results regarding urine output 14,15 .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation